Adhesion of Teeth - Zhao, Zhilong; Wang, Qihui; Zhao, Jing; Zhao, Bo; Ma, Zhangyu; Zhang, Congxiao (Frontiers in Materials, 2021)
Dental bonding materials are widely used in dentistry and there are several available kinds. However, in recent years, there has been no further research into dental bonding materials, with most dentists focusing on dental implants and orthodontics. In this paper, we systematically review the technology of tooth bonding in recent years and summarize the existing literature for potential innovation and direction of future research. First, the theoretical research on dental assembly materials and bonding mechanism was reviewed. Then, we reviewed the bonding of teeth, the bonding of metal alloy prosthesis, and the measurement of bond strength. Finally, the future development of dental bonding technology was evaluated. It is hoped that more dentists will be able to treat patients and update research on osteogenesis in the field of teeth bonding to bring a new era to the restoration of teeth in the future.